A note on differences of composition operators acting on the Hardy space - Dai, Jineng (MATHEMATICA SCANDINAVICA, 2022)
When $φ$ and $ψ$ are holomorphic self-maps of the unit disk with bounded multiplicity, we give a compact characterization for the difference of composition operators $C_φ $ and $C_ψ $ acting on the Hardy space, which extends a recent result in the case of univalent maps by Choe et al.